Enhancing golf swing performance through M1-targeted transcranial direct current stimulation: a double-blind, randomized crossover study - Xiang, Hongbin; Moon, Hwang Woon; Li, Lu; Yoo, Kyung (Frontiers in Sports and Active Living, 2025)
ObjectiveThis study investigated whether transcranial direct current stimulation (tDCS) targeting the primary motor cortex (M1) can induce acute enhancements on golf swing performance, particularly in tasks requiring long-driving distance capacity and accuracy control.MethodsEight professional golfers participated in a double-blind, randomized, crossover trial consisting of two conditions: active tDCS (A-tDCS) and sham tDCS (S-tDCS). Stimulation was applied over the left M1 for 20 min. Participants performed 10 swings each for three tasks (driver, iron, and wedge) both pre- and post-intervention. Performance metrics included long-driving distance variables (clubhead speed, ball speed, carry distance) and accuracy-related variables (face angle, side distance, and spatial error Data were analyzed using 2 × 2 repeated-measures ANOVAs, with post hoc t-tests and effect sizes (Hedge's g) where significant interactions were found.ResultsSignificant Time × Condition interactions indicated that A-tDCS improved carry distance and ball speed in iron tasks and carry distance in driver task (p < .05), with large effect sizes (g > 0.8). Side deviation also decreased significantly under A-tDCS in the iron task, indicating enhanced accuracy. No stimulation-specific effects were observed for the wedge task.ConclusionM1-targeted A-tDCS can acutely enhance golf swing long-driving distance capacity and accuracy in tasks requiring substantial force output. This technique is promising as a performance-enhancing tool for golfers, offering a low-fatigue alternative to traditional high-intensity training.